Evolución y desarrollo de la agricultura en Antioquia: una visión en términos de PIB (2016)
The development of agricultural sector activity in the country has always been an important factor for the national economy, although paradoxically in a country like ours whom counts on the geographic and climatic conditions to be a power in agricultural activities, this type of activities does not have the optimal development, much less the sufficient guarantees that allow a high productivity of the sector; in addition, the precarious conditions in which peasants develop their productive activities contribute to the unproductiveness of the countryside and the low living conditions of the people who inhabit it. In this article, it is initially considering the agricultural evolution in the country, explaining the background and origins of this activity, making a count of the history since 1950, also showing the participation of agriculture In the national GDP and especially in the department of Antioquia. Finally exposed a critical view of the current situation of agricultural activities in the country, in addition to criticism of labor development and the dehumanization of farmers conditions.